Interactions in IPM: plant, insect pest and pest control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
seminar, Insect pest control for smallholders: integrating biological control and host plant resistance, in Addis Ababa, Ethiopia, 9-13 October 1995